Effect of the sodium reduction and smoking system on quality and safety of smoked salmon (Salmo salar). - Muñoz, Israel; Guàrdia, Maria Dolors; Arnau, Jacint; Dalgaard, Paw; Bover, Sara; Fernandes, José O.; Monteiro, Carolina; Cunha, Sara C.; Gonçalves, Amparo; Nunes, Maria Leonor; Oliveira, Helena (Food and Chemical Toxicology, 2020)
Excessive sodium (Na) intake has been associated with high blood pressure and cardiovascular diseases. Therefore, sodium reduction is a public health challenge worldwide. The aim of this study was to develop smoked salmon with a reduced Na content. Sodium chloride (NaCl) was replaced by potassium chloride (KCl) at 25% and 50% (molar replacement) and studied in combination with two smoking procedures (natural wood and liquid smoke) as well as two smoking temperatures (18-19ºC or 56ºC). Smoked salmon samples were characterized by physicochemical, sensory and microbiological analyses. No major differences were observed regarding physicochemical properties in the studied treatments. Smoked samples with 50% of NaCl replaced by KCl were slightly more bitter than those with 25% whereas samples with 25% of replacement did not show differences to those with non-reduced Na content (5 g of added NaCl per 100 g of salmon). Molar Na:K ratio decreased from 4,3 in controls to 1,4 and 0,6 in samples with a NaCl reduction level of 25% and 50 % respectively. Microbiological assessment indicates that 2-week shelf-life would be appropriate and safe in terms of accomplishment of the EU regulation, taking into account foreseeable storage temperatures (up to 8 ºC). Thus, it is possible to achieve a reduction of 25-50% of NaCl in smoked salmon by replacing NaCl by KCl and considerer this product as a “source” of K. Dataset can be found at 10.5281/zenodo.4312939